Demographic and tumour prevalence data for juvenile green turtles at the Coastal-Marine Protected Area of Cerro Verde, Uruguay. Issue 5 (27th May 2016) - López-Mendilaharsu, Milagros; Vélez-Rubio, Gabriela M.; Lezama, Cecilia; Aisenberg, Anita; Bauzá, Antonia; Berrondo, Laura; Calvo, Victoria; Caraccio, Noel; Estrades, Andrés; Hernández, Martín; Laporta, Martín; Martínez-Souza, Gustavo; et al.
ABSTRACT: Marine Protected Areas are increasingly considered in coastal areas as an instrument to preserve threatened fauna and fragile habitats from the detrimental effects of human activities. For this reason baseline data are of utmost importance for the evaluation of the outcomes of ongoing conservation efforts. Along the Uruguayan coast, the area of Cerro Verde (declared protected since 2011) represents the most important foraging and development area for green turtles ( Chelonia mydas ). Between 2002 and 2009, a long-term capture-mark-recapture programme for green turtles was developed to gather data on demography, ecology and status of the species in the area. Turtles captured were juveniles ranging from 28.8 to 64.3 cm in length over the curve of the carapace ( n = 514), and results indicated a size-based habitat segregation. Tumour prevalence was 5.3% ( n = 27) and was positively correlated with carapace length. The mean body condition index was 1.25 ± 0.14 ( n = 494). From the total number of tagged turtles 10.6% were recaptured during the study period. Green turtles showed high site fidelity; 81% of the turtles were recaptured within the same season and 76% were recaptured in different seasons but were found at the original capture spot. Mean annual growth rate was 1.6 ± 0.9 cm year −1 . The catch per unit effort of 2008 differed from 2009, higher in 2009, but also significantly different between capture spots. The present study constitutes a baseline dataset for future monitoring of green turtles in the area and provides valuable information for wider analyses of population dynamics in the Southwestern Atlantic Ocean.